Bottom-up synthesized crystalline boron quantum dots with nonvolatile memory effects through one-step hydrothermal polymerization of ammonium pentaborane and boric acid. Issue 18 (20th April 2022) - Wang, Huiqi; Han, Jiacheng; Wang, Mei; Wang, Liyong; Jia, Suping; Cao, Honghong; Hu, Shengliang; He, Yan-Bing
Abstract : Crystalline BQDs are synthesized through a bottom-up strategy and used to fabricate a BQD–PVP memory device with nonvolatile rewritable memory effects. Abstract : Crystalline boron quantum dots (BQDs) are, for the first time, synthesized through a typical bottom-up approach by using ammonium pentaborane and boric acid as precursors under hydrothermal synthesis conditions. The results show that the as-prepared BQDs are evenly distributed with a narrow size of ca. 6.4 nm, good dispersibility and high stability in aqueous solution. As a novel application, a mixture of the as-prepared BQDs and polyvinyl pyrrolidone (PVP) is used as an active layer for the fabrication of a BQD–PVP memory device, which exhibits typical bistable electrical switching behavior and a nonvolatile rewritable memory effect with a high ON/OFF current ratio of more than 10 3 and good stability at a read voltage of 0.1 V. The ON/OFF current ratio of this device is high enough to ensure a low misreading rate through the precise control of the ON and OFF states, making the mixture of BQD–PVP have great potential in flash memory devices. The conduction mechanism of the BQD–PVP memory device is disclosed using the space-charge-limit current model. The charge injection/extraction behavior of the BQD–PVP active layer is investigated to clarify the electronic transition. The charge carriers were first injected into the PVP layer through a thermionic process, blocking the injection to the BQDs due to the large injection barrier between PVP and the BQDs. The charge carriers transferred between PVP and the BQDs and were finally trapped by the BQDs at a higher voltage. This work is desirable for low-voltage and overlong read cycle memory devices.